Analysis of Improving Mathematics Learning Outcomes through Realistic Mathematics Education in Grade IV Students of SD Negeri 9 Sila - Atmaja, Jessy Parmawati (Lembaga Penelitian dan Pendidikan Mandala, 2024)
The purpose of this study is to improve mathematics learning outcomes through Realistic Mathematics Education (PMR) for grade IV students of SD Negeri 9 Sila on the material Build a Simple Space. This research is a Classroom Action Research (PTK) with a design according to Kemmis and Mc.Taggart. The research subjects used were 26 grade IV students of SD Negeri 9 Sila. The data collection techniques used are observation and tests. Data analysis uses qualitative descriptive and quantitative descriptive analysis. The results of classroom action research show that the application of Realistic Mathematics Education (PMR) can improve the learning process and student mathematics learning outcomes. In the pre-action, there were 7 students (26.9%) who achieved the Minimum Completeness Criteria (KKM). In the first cycle as many as 15 students (57.7%) have achieved the Minimum Completeness Criteria (KKM) and in the second cycle as many as 24 students (92.3%) have achieved the Minimum Completeness Criteria (KKM).